Avenues of Translation : The City in Iberian and Latin American Writing - Scaramella, Evelyn; Galasso, Regina (Book collections on Project MUSE., 2019)
Cities both near and far communicate in a variety of ways. Travel between, through, and among urban centers initiates contact, and cities themselves are sites of ever-changing cultural and historical encounters. Predictable and surprising challenges and opportunities arise when city borders are crossed, voices meet, and artistic traditions find their counterparts. Using the Latin word for "translation," translatio, or "to carry across," as a point of departure, Avenues of Translation explores how translation perpetuates, diversifies, deepens, and expands the literary production of cities in their greater cultural context, and how translation shapes an understanding of and access to a city's past and present literary and cultural practices. Thinking about translation and the city is a way to tell the backstories of the cities, texts, and authors that are united by acts of translation. Published by Bucknell University Press. Distributed worldwide by Rutgers University Press.